Addiction Research Centres and the Nurturing of Creativity. Monitoring the European drug situation: the ongoing challenge for the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA) - Griffiths, Paul; Mounteney, Jane; Lopez, Dominique; Zobel, Frank; Götz, Wolfgang (Addiction (Abingdon, England), 2012)
ABSTRACT The European Monitoring Centre for Drugs and Drug Addiction (EMCDDA) is the designated hub for drug‐related information in the European Union. The organization's role is to provide the European Union (EU) and its Member States with a factual overview of European drug problems and a common information framework to support the drugs debate. In order to achieve its mission, the EMCDDA coordinates and relies on a network of 30 national monitoring centres, the Reitox National Focal Points. The Centre publishes on a wide range of drug‐related topics, across epidemiology, interventions, laws and policies. Every November, the EMCDDA publishes its Annual Report, providing a yearly update on the European drug situation, translated into 23 EU languages. In line with its founding regulation, the EMCDDA has a role acting as an interface between the worlds of science and policy. While not a research centre in the formal sense, the results the Centre generates serve as catalysts for new research questions and help to identify priorities. Current challenges facing the agency include continuing to increase scientific standards while maintaining a strong institutional role, as well as supporting European efforts to identify, share and codify best practice in the drugs field.